Design and fabrication of r-hirudin loaded dissolving microneedle patch for minimally invasive and long-term treatment of thromboembolic disease - Mengfang Wu; Tian Xia; Yaran Li; Tianfa Wang; Shijia Yang; Jinchao Yu; Qiaoyan Liang; Teng Shen; Min Yu; Bing Zhao (Elsevier, 2022)
Cardiovascular disease is the leading cause of global mortality, with anticoagulant therapy being the main prevention and treatment strategy. Recombinant hirudin (r-hirudin) is a direct thrombin inhibitor that can potentially prevent thrombosis via subcutaneous (SC) and intravenous (IV) administration, but there is a risk of haemorrhage via SC and IV. Thus, microneedle (MN) provides painless and sanitary alternatives to syringes and oral administration. However, the current technological process for the micro mould is complicated and expensive. The micro mould obtained via three-dimensional (3D) printing is expected to save time and cost, as well as provide a diverse range of MNs. Therefore, we explored a method for MNs array model production based on 3D printing and translate it to micro mould that can be used for fabrication of dissolving MNs patch. The results show that r-hirudin-loaded and hyaluronic acid (HA)-based MNs can achieve transdermal drug delivery and exhibit significant potential in the prevention of thromboembolic disease without bleeding in animal models. These results indicate that based on 3D printing technology, MNs combined with r-hirudin are expected to achieve diverse customizable MNs and thus realize personalized transdermal anticoagulant delivery for minimally invasive and long-term treatment of thrombotic disease.